The Traditional Chinese Medicine nursing experience of a case of refractory oral lichen planus with systemic skin lesions (1例难治性口腔扁平苔藓伴全身皮损的中医护理体会) - LI Qi (李琪); HUANG Ying (黄颖); ZHANG Qinyu (张沁玉); WEN Wen (文文) (Association of Integrative Nursing, 2021)
This paper summarized the Traditional Chinese Medicine nursing experience of a case of refractory oral lichen planus with systemic skin lesions. Nursing interventions included monitoring of patient's medical condition, especially condition of oral mucosa and skin injury; monitoring of adverse drug reaction during medication; enhancing the skin care; providing dietary instruction by differentiation of syndrome and reducing the food-induced local irritants; carrying out psychological nursing; enhancing the patient's awareness the disease and physical conditions by health education. (本文总结1 例难治性口腔扁平苔藓伴全身皮损患者的中医护理经验。护理人员严密观察患者病情变化, 尤其是口腔黏膜及皮肤病损变化; 在中药内服期间, 严密观察患者用药效果及不良反应; 加强皮肤护理; 给予科学的饮食指导, 辨证施膳, 减轻食物对口腔黏膜的理化刺激; 给予情志护理, 调和五脏六腑; 护理人员加强对患者的健康教育, 增加患者的认知, 帮助患者增强体质, 抵御外邪入侵。)